STUDI KEANEKARAGAMAN IKAN KARANG DI PULAU JANGGI KECAMATAN TAPIAN NAULI KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - Arief Rahman Hakim; Eri Yusni; Zulham Apandy Harahap (AQUACOASTMARINE, 2018)
The reseacrh aimed to determine reef fish diversity index, uniformity index of reef fish, reef fish species composition, percentage of reef fish and water quality. The research in was conducted on March, 2016, which was located in theJanggi Island NauliTapian Central Tapanuli, North Sumatra. The method used in the research is Underwater Fish Visual Census (Underwater Visual Census/ UVC) on two points of the station with the line length of 50 m and a width transect each to left and right as many as 5 m and three replications, observations had done for 15- 20 minutes.The quality index of reef fish diversity in Janggi Island was low category (H ' ≤ 2.0). Results of analysis of the data for evenness index of target fish, major fish and indicator fish categorized as low (0 <E ≤ 0.5). For the composition of reef fish species were found 30 species and 8 families, the highest analysis contained on major fish at 69%, target fish at 21% and the lowest at 10% is indicator fish.Keyword : Underwater Visual Census, Transect,Reef Fish, Janggi Island, Tapanuli Tengah District